The Importance of Field Training in Botany in the Educational Process of Higher Education Institutions (Journal of Educational Sciences, 2026)
The article examines the role of field-based learning in enhancing students’ academic and cognitive activity and developing their professional skills. The aim of the study is to analyze the importance of forming practical competencies that contribute to acquiring high-quality education and achieving success in a professional career. Field practice in botany provides conditions for students’ professional and personal growth and facilitates in-depth mastery of the scientific field. By combining theory with practice and working with real-life examples in the field, students clarify their professional orientation.Achieving high-quality education is possible when students engage in independent inquiry and develop their creative abilities. Therefore, the practical training stage is considered an essential component in preparing future competitive and competent specialists. The study involved a survey aimed at identifying the benefits of field practice for students during their university studies and for graduates in their professional careers. The survey questions focused on the role of botanical field research in mastering scientific methods and approaches, as well as the level of support provided to students. Analysis of the survey results revealed that academic success and professional development are closely linked to the skills acquired during practice. This study provides valuable insights for universities, master’s and doctoral students in teaching biology and developing scientific competencies, highlighting the importance of field-based learning.Keywords: botany, field training, educational process, educational and cognitive activity.